Identifying the risk of dyslexia in bilingual children: The potential of language-dependent and language-independent tasks - Taha, Juhayna; Carioti, Desire; Stucchi, Natale; Chailleux, Mathilde; Granocchio, Elisa; Sarti, Daniela; De Salvatore, Marinella; Guasti, Maria Teresa (Frontiers in Psychology, 2022)
This study investigates the linguistic processing and non-linguistic cognitive abilities of monolingual and bilingual children with and without reading difficulties and examines the relationship between these skills and reading. There were 72 Italian-speaking children: 18 monolingual good readers (MONO-GR, Mage = 10;4), 19 monolingual poor readers (MONO-PR, Mage = 10;3), 21 bilingual good readers (BI-GR, Mage = 10;6), and 16 bilingual poor readers (BI-PR, Mage = 10;6). All bilingual children spoke Italian as their L2. Children completed a battery of standardized Italian reading tests, language-dependent tasks: nonword repetition (NWR), sentence repetition (SR), and phonological awareness (PA), and language-independent tasks: timing anticipation, beat synchronization, inhibition control, auditory reaction time, and rapid automatized naming (RAN). Poor readers scored below good readers on the language-dependent tasks, including NWR, PA, and SR. Beat synchronization was the only language-independent task sensitive to reading ability, with poor readers showing greater variability than good readers in tapping to fast rhythms. SR was the only task influenced by language experience as bilinguals underperformed monolinguals on the task. Moreover, there were weak to moderate correlations between performance on some language-dependent tasks (NWR, PA), language-independent tasks (inhibition control, RAN), and reading measures. Performance on the experimental tasks (except for RAN) was not associated with the length of exposure to Italian. The results highlight the potential of NWR, PA, SR, and beat synchronization tasks in identifying the risk of dyslexia in bilingual populations. Future research is needed to validate these findings and to establish the tasks’ diagnostic accuracy.